Nickel Cluster Growth on Defect Sites of Graphene: A Computational Study1. Issue 52 (8th November 2013) - Gao, Wang; Mueller, Jonathan E.; Anton, Josef; Jiang, Qing; Jacob, Timo
<x xml:space="preserve">Abstract</x> Watching the defectives: DFT studies on the growth of nickel clusters on different graphene substrates shows that graphene defects essentially determine the morphology of the clusters. Defects greatly improve the catalytic reactivity of the larger clusters Nin (5≤n≤10). Smaller clusters Nin (n<4) efficiently open the band gap of defective graphene, allowing a way to modulate the electronic properties of the graphene.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>